2022
DOI: 10.1371/journal.pone.0264617
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lifestyle changes during coronavirus disease 2019 pandemic in Gondar town, Northwest Ethiopia

Abstract: Background Coronavirus disease 2019 has had a global effect on people’s lifestyles. Many people have developed irregular eating patterns and become physically inactive, which leads to an aggravation of lifestyle-related diseases and unhealthier lifestyles; these, subsequently raise the severity of coronavirus disease 2019. This study aimed to assess lifestyle changes during coronavirus disease 2019 pandemic in Gondar town, North West, Ethiopia. Method Community-based cross-sectional study design was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…On the other hand, in Italy, exercise frequency increased and was done at home among those who already took part in sports, and those who used to exercise only occasionally before [ 13 ]. In Ethiopia, adopting PA increased after the pandemic in the form of performing household chores [ 40 ]. This difference in findings between studies may be attributed to the different cultures, availability of recreation places, and different methods of PA assessment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Italy, exercise frequency increased and was done at home among those who already took part in sports, and those who used to exercise only occasionally before [ 13 ]. In Ethiopia, adopting PA increased after the pandemic in the form of performing household chores [ 40 ]. This difference in findings between studies may be attributed to the different cultures, availability of recreation places, and different methods of PA assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome-coronavirus (SARS-CoV-2) pandemic has changed the pattern of our lives within a couple of years or more. 1,2 Since early 2020, COVID-19 has spread rapidly around the world, exceeding 620 million cases and 6 million deaths as of October 2022. 3,4 One of the reasons COVID-19 spreads so quickly is transmission during the incubation period, which was reported to 5.1 days 5,6 for alpha-variant, 4.4 days for delta-variant, 7 and 3.1 days for omicron-variant.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome‐coronavirus (SARS‐CoV‐2) pandemic has changed the pattern of our lives within a couple of years or more 1,2 . Since early 2020, COVID‐19 has spread rapidly around the world, exceeding 620 million cases and 6 million deaths as of October 2022 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19, an acute respiratory infection that initially emerged in China and is caused by SARS-CoV-2, developed into a global pandemic [ 18 ]. The pandemic has altered many aspects of lifestyle behaviours, including physical activity, decreased outdoor activities, altered sleep, social distancing, prolonged isolation and dietary habits, which have led to weight gain and other conditions during the lockdown period [ 19 , 20 , 21 , 22 ]. Recent large observational studies have reported varying prevalence rates of vitamin D deficiency, including 37% (Canada), 24% (USA), and 40% (Europe).…”
Section: Introductionmentioning
confidence: 99%